2013
DOI: 10.1371/journal.pntd.0002254
|View full text |Cite
|
Sign up to set email alerts
|

Immunoprotection of Mice against Schistosomiasis Mansoni Using Solubilized Membrane Antigens

Abstract: BackgroundSchistosomiasis continues to be one of the most prevalent parasitic diseases in the world. Despite the existence of a highly effective antischistosome drug, the disease is spreading into new areas, and national control programs do not arrive to complete their tasks particularly in low endemic areas. The availability of a vaccine could represent an additional component to chemotherapy. Experimental vaccination studies are however necessary to identify parasite molecules that would serve as vaccine can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 71 publications
0
14
0
Order By: Relevance
“…cidence and prevalence into new countries (Sulbara et al, 2013). Basyoni and Abd El-Wahab ( 2013) reported that B. alexandrina antigen was good one among other antigens that can replace adult S. mansoni crude antigen in diagnosis and thus for vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…cidence and prevalence into new countries (Sulbara et al, 2013). Basyoni and Abd El-Wahab ( 2013) reported that B. alexandrina antigen was good one among other antigens that can replace adult S. mansoni crude antigen in diagnosis and thus for vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…S. mansoni adult worms ["JL strain, Venezuela," maintained at the Instituto Venezolano de Investigaciones Científicas (IVIC) Trematodiasis Unit] were obtained by perfusion from the portal vein of golden hamsters infected with 500 cercariae (16). All procedures involving animals were performed according to the National Guidelines for Laboratory Animals established by the "Asociación Venezolana de Bioterios."…”
Section: Methodsmentioning
confidence: 99%
“…Our interest in these muscles was catalyzed by reports that the drug used to treat schistosomiasis (praziquantel) may act on the myosin molecule (15), and that muscle proteins like myosin, paramyosin, and certain regions of actin might be useful targets for the development of an antischistosomal vaccine or chemotherapy (16)(17)(18). We show that the adult form of S. mansoni has exclusively smooth muscles, and yet its thick filaments have the bipolar, helical structure characteristic…”
mentioning
confidence: 90%
“…Treatment of adult schistosome worm tegument with sub-curative PZQ enhanced its protective effects: in vitro TT induced the highest protection value by 51.8–57%, and in vivo TT caused 44.6–50.2% reductions in the adult worm burden when compared to the PBS + adjuvant. This level of protection was comparable to tegumental preparations so far used in murine schistosomiasis vaccine, such as tegumental glycosyl phosphatidyl inisotol (GPI)-anchored proteins that induced 42% reduction of the adult worm burden (Martins et al , 2012), use of an n-butanol extract of adult S. mansoni worm membrane fraction that resulted in 40.7–62.4% fewer adult worms than in control mice (Sulbaran et al ., 2013), and fused Sm14/29 formulated with polyinosinic-polycytidylic acid adjuvant (polyI:C) that induced 48.4% protection (Mossallam et al , 2015). Furthermore, in vitro TT induced the highest reduction in tissue egg numbers, followed by in vivo TT.…”
Section: Discussionmentioning
confidence: 99%